Proculturation shaped by social representations of academic migrants from Italy to the United States - Dryjanska, Laura (Frontiers in Psychology, 2023)
Introduction Existing literature has highlighted the phenomenon of academic migrants leaving Italy for the United States with the hope of finding institutions that offer more opportunities for growth and recognition based on merit, as opposed to corruption, nepotism, and excessive bureaucracy. Likely, these may be the expectations of Italian academic migrants, who seem to be thriving and flourishing in their careers. This paper discusses proculturation of academic migrants from Italy to the United States, in the light of their expectations related to self-concept as well as social representations of North American university instructors from transnational families. Methods In this study, 173 participants volunteered to provide information in an online survey that included their demographic profile, family situation, language ability, recalled pre-migration expectations and preparations, satisfaction with life, self-perceived stress, self-rated health, free responses to questions about major successes, challenges, and goals, as well as self-identification. Results The results have shown that participants were indeed thriving in their careers and lives (majority scored high in satisfaction with life, health, realistic expectations and helpful per-migration preparations, while low in stress, also indicating work-related accomplishments and successes), but somewhat struggled with proculturation-related issues, frequently mentioned among major challenges.